ANALISIS KETERSEDIAAN DAN PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI DI MADRASAH IBTIDAIYAH SYEKH MANSHUR PANDEGLANG - Rosita, Desyi; Hidayatullah, Agus; Aminudin, Aminudin (Staisman Press, 2024)
Technology-based learning media has become an important concern in increasing the effectiveness of learning at Madrasah Ibtidaiyah Syekh Manshur Pandeglang. This research aims to analyze the availability and use of technology-based learning media at Madrasah Ibtidaiyah Syekh Manshur Pandeglang. The research method used is a descriptive method with a quantitative approach. Data collection was carried out through questionnaires distributed to teachers at Madrasah Ibtidaiyah Syekh Manshur Pandeglang. Apart from that, observations were also carried out to directly observe the availability of technology-based learning media in the madrasah. The research results show that although there are several technology-based learning media available at Madrasah Ibtidaiyah Syekh Manshur Pandeglang, their use is still limited. Factors such as the availability of devices, teacher skills in operating technology, and support from the school are things that influence the use of technology-based learning media. It is hoped that this research can provide input for the development of learning strategies at Madrasah Ibtidaiyah Syekh Manshur Pandeglang, especially in increasing the use of technology-based learning media as a means of supporting a more interactive and effective learning process.